1999
DOI: 10.1590/s0100-879x1999000200013
|View full text |Cite
|
Sign up to set email alerts
|

Trans-sialidase delivered as a naked DNA vaccine elicits an immunological response similar to a Trypanosoma cruzi infection

Abstract: Trypanosoma cruzi, the protozoan parasite that causes Chagas disease, does not synthesize sialic acid, but expresses a trans-sialidase (TS) that catalyzes the transfer of sialic acid from host glycoconjugates to the parasite surface. Here, we review studies that characterize the immune response to the catalytic domain of the enzyme in humans during Chagas disease or in mice following immunization with the TS gene. In both cases, there are antibodies that strongly inhibit the enzymatic activity and generation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 24 publications
(22 reference statements)
1
15
0
Order By: Relevance
“…The enzyme's N-terminal domain is responsible for the induction of specific antibodies that inhibit the enzymatic activity of TS during infection (14,23,24). Moreover, the N-terminal domain has important roles in the humoral (6,15,23) and cellular (26,27) immune responses that control infection. Therefore, we aimed to investigate whether sera from patients with Chagas' disease specifically recognize this recombinant TS and if this recognition decreases in patients undergoing anti-T. cruzi chemotherapy with benznidazole.…”
mentioning
confidence: 99%
“…The enzyme's N-terminal domain is responsible for the induction of specific antibodies that inhibit the enzymatic activity of TS during infection (14,23,24). Moreover, the N-terminal domain has important roles in the humoral (6,15,23) and cellular (26,27) immune responses that control infection. Therefore, we aimed to investigate whether sera from patients with Chagas' disease specifically recognize this recombinant TS and if this recognition decreases in patients undergoing anti-T. cruzi chemotherapy with benznidazole.…”
mentioning
confidence: 99%
“…In the human pathogen Trypanosoma cruzi, the ethiological agent of Chagas' disease, there are mucin-type glycoproteins that have been increasingly studied because of their role as the main sialic acid acceptors (1,2) in the reaction catalyzed by transsialidase (3,4). This unique enzymatic activity seems to have been selected during evolution to circumvent the lack of de novo synthesis of this sugar in this protozoan parasite (5).…”
mentioning
confidence: 99%
“…Because of their size and structure, T. cruzi mucins are comparable to endothelial mucin-type adhesion molecules, better than to high molecular weight epithelial mucins. Additionally, T. cruzi being a digenetic parasite, there are at least two different groups of mucin molecules among life cycle stages: one present in the insect vector forms of the parasite and the other in the mammalian stage (2). T. cruzi infection is established in the mammal by the insect-derived stage metacyclic trypomastigote.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…DNA vaccines encoding the catalytic domain of TS have been shown to induce immunity protective against systemic T. cruzi challenge (3,4,6,16). It has also been shown that both CD4 ϩ and CD8 ϩ T-cell epitopes are required for this TS-specific protective immunity (6).…”
Section: Ts Is An Immunodominant Protein Inducing Strong Antibody Andmentioning
confidence: 99%